(untitled) (Development Service Industry Management, 2025)
Falsification and food fraud are global issues that threaten food safety, consumer health, and the stability of the agri-food sector. These practices involve the intentional adulteration, mislabeling, or substitution of products for economic gain, causing health risks, financial losses, and damage to public trust. In Ukraine, this problem is particularly pressing due to complex supply chains, limited control systems, the shadow segment of the market, and insufficient use of modern traceability and digital monitoring technologies. The situation is further complicated by the impact of war, logistical disruptions, and the reorientation of export flows, which create additional opportunities for dishonest practices. The article analyzes key types of food fraud – adulteration, mislabeling, counterfeiting, and substitution – and their consequences for consumers, honest producers, and the country’s international reputation. Special attention is given to products with “credence attributes” such as organic, GMO-free, geographical indications, or ethically produced goods, where verification is difficult and risks of deception are high. Such cases undermine fair competition, distort price signals, and erode public confidence in food quality systems, certification schemes, and state oversight institutions. Modern strategies to combat food fraud are reviewed, including regulatory improvements, the harmonization of Ukrainian legislation with EU law, technological innovations (DNA testing, isotope analysis, blockchain-based traceability, digital product passports), and cooperation among control institutions, laboratories, business associations, and consumer organizations. The article emphasizes that effective prevention requires risk-based control, transparent information systems, and continuous communication between government, business, and civil society. Recommendations include short-term measures (stricter control and penalties, targeted inspections of high-risk categories), medium-term steps (technological modernization of laboratories and control bodies, development of national databases and e-registers), and long-term reforms to fully align Ukraine’s food safety and quality system with EU standards within the framework of European integration. Implementing these actions will strengthen transparency, reduce incentives for fraud, restore consumer trust, and enhance the overall resilience and competitiveness of the national food sector in domestic and foreign markets.